2007
DOI: 10.1016/j.cellsig.2007.07.017
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of anterograde transport of adrenergic and angiotensin II receptors by Rab2 and Rab6 GTPases

Abstract: Three Rab GTPases, Rab1, Rab2 and Rab6, are involved in protein transport between the endoplasmic reticulum (ER) and the Golgi. Whereas Rab1 regulates the anterograde ER-to-Golgi transport, Rab2 and Rab6 coordinate the retrograde Golgi-to-ER transport. We have previously demonstrated that Rab1 differentially modulates the export trafficking of distinct G protein-coupled receptors (GPCRs). In this report, we determined the role of Rab2 and Rab6 in the cell surface expression and signaling of α 2B -adrenergic (α… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
54
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 56 publications
0
54
0
Order By: Relevance
“…In contrast, much less is known about the involvement of Rab GTPases in GPCR export from the Golgi to the plasma membrane. Our previous studies have demonstrated the roles of several Rab GTPases in regulating GPCR transport along the early secretory pathway (25)(26)(27)(28)(29). In this article, we expand these studies to determine the role of Rab8 GTPase in the cell surface targeting of ␣ 2B -AR and ␤ 2 -AR and the possible mechanism involved.…”
mentioning
confidence: 90%
See 3 more Smart Citations
“…In contrast, much less is known about the involvement of Rab GTPases in GPCR export from the Golgi to the plasma membrane. Our previous studies have demonstrated the roles of several Rab GTPases in regulating GPCR transport along the early secretory pathway (25)(26)(27)(28)(29). In this article, we expand these studies to determine the role of Rab8 GTPase in the cell surface targeting of ␣ 2B -AR and ␤ 2 -AR and the possible mechanism involved.…”
mentioning
confidence: 90%
“…The PCR product was digested with XhoI and HindIII, purified, and ligated to 3HA-tagged pcDNA3.1(Ϫ) vector, which was digested with XhoI and HindIII. The GFP and HA epitopes have been used to label GPCRs, including ␣ 2B -AR and ␤ 2 -AR, resulting in receptors with similar characteristics to the wildtype receptors (12,29,38,39).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Retrograde transport to the ER is likely involved in re-targeting misfolded proteins to the ERAD 28 . Other defective proteins are targeted to lysosomal degradation after sorting to endosomes 28 Perturbing the function of the Rab6 GTPAse, which regulates vesicular transport in the Golgi 30 , inhibited the anterograde transport of Drosophila rhodopsin 31 and of mammalian GPCRs 25 . There is no evidence for GPCR sorting from the Golgi to endosomes or ER and it remains unknown whether GPCR targeting to the cell surface from the Golgi is regulated.…”
Section: Post Er Traffickingmentioning
confidence: 99%